SPATIAL ANALYSIS: PENDEKATAN METROPOLITAN STATISTICAL AREA UNTUK PERENCANAAN PEMBANGUNAN MANUSIA DI PROVINSI JAWA TENGAH - Khotimah, Dian Rizqi Khusnul (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
Human development is one of the main focus of development in National Medium-Term Development Plan (RPJMN) 2020-2024. This is stated in the third of seven development agendas, "Improving Quality and Competitive Human Resources". Level of human development can be reflected through the Human Development Index (HDI). In 2020, HDI of Central Java Province is 71,87. It has reached the high-level category (70-80), but it is closer to the medium-level category (<70). HDI of Central Java Province in 2020 occupied only on the 13th position among 34 other provinces. There is a need for optimizing the conditions of human development in Central Java Province. Mapping on the quality of human development contributes to ensure equitable distribution of competencies in order to accelerate national economic recovery during pandemic. Therefore, this study aims to identify, map, and determine priority areas for human development in Central Java Province as recommendations for government in making policies. There are three different analysis method, they are descriptive analysis, spatial analysis with Moran's and LISA, and Metropolitan Statistical Area (MSA) to determine development priority areas. The variable of study is HDI values for 35 districts in Central Java Province. The result of descriptive analysis describes that the western region of Central Java Province tends to has a lower of HDI values than the center to eastern side. Based on geospatial linkages and MSA approach, the human development planning in Central Java Province should focus on the three MSA formed, namely MSA Tegal, MSA Pekalongan, and MSA Purworejo as the development priority areas.